Peran Instagram Sebagai Media Promosi Untuk Mempertahankan Pelanggan Pada Event Organizer PT. Pagador Kreasi Mandiri - Anisa Lubna; Zike Martha (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
In the midst of the rapid development of social media, the event organizer industry is experiencing significant growth. The number of new event organizer companies that have emerged has made the market increasingly competitive, many business actors rely on price war strategies to attract customers. One of them is PT. Pagador Kreasi Mandiri which operates in the field of activity organizing services or is called an event organizer, be it gathering activities, especially outbound offroading and rafting. In facing these challenges, Instagram has become a very important tool for event organizer companies to remain relevant and competitive without having to get caught in a price war. Instagram allows event organizer companies to promote services through attractive visual content and highlight qualities that can differentiate them from other competitors. The theory used in this research is the marketing communication mix theory. The method used in this research is a qualitative descriptive approach. The techniques used in this research are interview techniques, observation techniques and documentation techniques. Data analysis techniques used in qualitative research include data reduction, data presentation and drawing conclusions. The data in this study was tested using data source triagulation. Based on the results of research regarding the role of Instagram as a promotional media to retain customers at event organizers PT. Pagador Kreasi Mandiri. Following are some of the main elements in the marketing communication mix used by PT. Pagador Kreasi Mandiri. Advertising via social media Instagram, by publishing video content via reels and Instastory features on Instagram @pagador_team. The role of Instagram as a promotional media at PT. Pagador Kreasi Mandiri is contacting customers via Direct Massage (DM) on Instagram with the aim of building relationships with potential customers and maintaining loyal customers, increasing sales and income. Personal selling used by PT. Pagador Kreasi Mandiri in promoting event organizers uses the Q&A and Live features on Instagram social media to integrate directly with customers. PT. Pagador Kreasi Mandiri uses sales promotions that provide special discount offers or vouchers to followers through posts or Stories, encouraging them to make immediate purchases